2005
DOI: 10.4269/ajtmh.2005.72.320
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Shedding of West Nile Virus in Urine of Experimentally Infected Hamsters

Abstract: Adult hamsters that survived experimental West Nile virus (WNV) infection developed persistent viruria. Infectious WNV could be cultured from their urine for up to 52 days. Immunohistochemical examination of kidneys of viruric animals showed foci of WNV antigen in renal tubular epithelial and vascular endothelial cells. These findings are compatible with virus replication and persistent infection of renal epithelial cells. The potential clinical and virologic significance of these findings as well as their pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
82
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 31 publications
(54 reference statements)
7
82
1
Order By: Relevance
“…Taken together, the results obtained for ROCV here and those reported in other studies for different flaviviruses , Tonry et al 2005, Siirin et al 2007 suggest that a variety of flaviviruses cause persistent infections in vertebrates and that the persistence of these viruses is not a rare phenomenon. However, further studies are needed to determine exactly how a persistent ROCV infection is established, including the route by which the virus enters the CNS, the cells that permit infection of the CNS and the cell groups involved in the production of virus and in the protective immune response, as well as other aspects of pathogenesis.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Taken together, the results obtained for ROCV here and those reported in other studies for different flaviviruses , Tonry et al 2005, Siirin et al 2007 suggest that a variety of flaviviruses cause persistent infections in vertebrates and that the persistence of these viruses is not a rare phenomenon. However, further studies are needed to determine exactly how a persistent ROCV infection is established, including the route by which the virus enters the CNS, the cells that permit infection of the CNS and the cell groups involved in the production of virus and in the protective immune response, as well as other aspects of pathogenesis.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, in an experimental study, Siirin et al (2007) demonstrated that adult hamsters infected with Saint Louis encephalitis virus continued to excrete the virus in urine for a prolonged period of time despite a robust immune response. These findings were similar to those reported for chronic infections with West Nile virus , Tonry et al 2005.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In contrast to neurons and macrophages, these latter cells do not die following infection. Instead they survive and often become persistently infected (21,22,29). Consistent with these results, we show that in vitro infection of macrophages with either Dengue-2 or Modoc virus results in cell killing similar to that of CPT at 48 hpi, whereas infection with either virus fails to kill renal epithelial cells and fibroblasts (MDCK, 293T, Vero, SW primary MEF, and C57/Bl primary MEF) even when the cells are infected at extremely high titer (m.o.i.…”
Section: Discussionmentioning
confidence: 99%
“…Because WNV is a neurotropic virus, its pathology in the CNS has been the focus of many studies; therefore, little is known about WNV pathogenesis in organs other than the CNS. Studies of WNV in birds, dogs, and rodents have shown that the kidney is a site of replication (7)(8)(9); moreover, infectious WNV has been recovered from urine samples from experimentally infected hamsters as early as day 1 to day 52 postinfection (9). The purpose of this study was to determine whether WNV is similarly shed in the urine of humans with WNV infections.…”
mentioning
confidence: 99%